ANALISIS YURIDIS TERHADAP PUTUSAN NOMOR.553/PID.B/2019/PN.Pbr TERHADAP TINDAK PIDANA PEMERASAN - Vitta Adelina Hutasoit; Evi Deliana; Davit Rahmadan (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2020)
Judge's decision is a judge's statement uttered in an open court session, which can be in the form of conviction or acquittal or exemption from all legal claims in matters and according to methods regulated in the Criminal Procedure Law In criminal procedural law, the objectives are set forth in the guidelines for the implementation of the Criminal Procedure Code issued by the Minister of Justice, namely: